Stratigraphy of the Dungan Group in Kach-Ziarat Area, N.E. Balochistan - Kazmi, Ali H. (Journal of Himalayan Earth Sciences, 1988)
A sequence of thick bedded to massive foraminiferal limestone inter-bedded with shale, underlain by argillaceous beds, commonly referred to as "Dungan limestone" or "Dungan Group" and ranging in age from Late Cretaceous to Palaeocene, occurs extensively in the northeastern Balochistan. The lithostratigraphy of this group is fairly consistent in the Harpai, Ziarat and Quetta areas, but changes laterally when traced east and southwest of this region. These variations in its lithology have led to the coining of several formation names within this group by various workers and has caused much confusion. It is, therefore, proposed that the Kach-Ziarat area be taken as the standard area for the Dungan Group because not only these rocks attain their maximum thickness here but are also easily accessible and entire sequence can be seen along a flat nearly horizontal footpath that follows the Anagan Gat nala just south of Ziarat. The lithostratigraphy and biostratigraphy of the Dungan Group has been studied and traced laterally over a large area. It is proposed that more detailed litho- and bio-stratigraphic studies are needed before a satisfactory division of this group into smaller units (formations and members) can be evolved. Pending such studies, it is suggested that the Dungan Group may be considered to comprise essentially two main formations-the Dungan Limestone (Maestrichtian to Palaeocene, at places ranging upto Lower Eocene) and the Bibai Formation (Companian to Maestrichtian). The Dungan Limestone may, however, be further sub-divided into an upper and a lower member.